Influencing factors for prevention of postpartum hemorrhage and early detection of childbearing women at risk in Northern Province of Rwanda: beneficiary and health worker perspectives - Oliva Bazirete; Manassé Nzayirambaho; Aline Umubyeyi; Marie Chantal Uwimana; Marilyn Evans (BMC, 2020)
Abstract Background Reduction of maternal mortality and morbidity is a major global health priority. However, much remains unknown regarding factors associated with postpartum hemorrhage (PPH) among childbearing women in the Rwandan context. The aim of this study is to explore the influencing factors for prevention of PPH and early detection of childbearing women at risk as perceived by beneficiaries and health workers in the Northern Province of Rwanda. Methods A qualitative descriptive exploratory study was drawn from a larger sequential exploratory-mixed methods study. Semi‐structured interviews were conducted with 11 women who experienced PPH within the 6 months prior to interview. In addition, focus group discussions were conducted with: women's partners or close relatives (2 focus groups), community health workers (CHWs) in charge of maternal health (2 focus groups) and health care providers (3 focus groups). A socio ecological model was used to develop interview guides describing factors related to early detection and prevention of PPH in consideration of individual attributes, interpersonal, family and peer influences, intermediary determinants of health and structural determinants. The research protocol was approved by the University of Rwanda, College of Medicine and Health Sciences Institutional Ethics Review Board. Results We generated four interrelated themes: (1) Meaning of PPH: beliefs, knowledge and understanding of PPH: (2) Organizational factors; (3) Caring and family involvement and (4) Perceived risk factors and barriers to PPH prevention. The findings from this study indicate that PPH was poorly understood by women and their partners. Family members and CHWs feel that their role for the prevention of PPH is to get the woman to the health facility on time. The main factors associated with PPH as described by participants were multiparty and retained placenta. Low socioeconomic status and delays to access health care were identified as the main barriers for the prevention of PPH. Conclusions Addressing the identified factors could enhance early prevention of PPH among childbearing women. Placing emphasis on developing strategies for early detection of women at higher risk of developing PPH, continuous professional development of health care providers, developing educational materials for CHWs and family members could improve the prevention of PPH. Involvement of all levels of the health system was recommended for a proactive prevention of PPH. Further quantitative research, using case control design is warranted to develop a screening tool for early detection of PPH risk factors for a proactive prevention.